55 Palliative care for people with motor neurone disease. An integrative literature review. Issue 3 (1st September 2018) - Hollowood, Lorna
Abstract : Motor neurone disease (MND) is a rare progressive neurodegenerative disease which results in muscle weakness reduced mobility dysphagia and speech and breathing difficulties with no curative treatment or remission where 50% of patients die within three years of their first symptom and many dying within a year of diagnosis (Whitehead et al. 2012 Wood-Allum 2014). Access to palliative care for people with motor neurone disease (MND) is an area of concern for the person with the condition as well as the carers supporting them (NICE 2016). This literature review examines the specific challenges in palliative care for people with MND and their carers. A systematic search was undertaken of the literature yielding 534 articles. This was reduced by inclusion and exclusion criteria to 43 articles which were selected for critical appraisal for their relevance to the topic using MacKenzie et al's (2010) quality review tool resulting. 16 articles were themed using Thomas and Harden's (2008) thematic analysis approach. Four themes emerged from the literature: the specific needs of carers of people with MND; Service provision; hope and depression and ethical decision-making. Despite a lack of quantifiable data relating to specialist palliative care to improve palliative outcomes in people with MND the literature shows that MND patents and their care-givers have a great need for integrated services which are equipped to deal with their very specific needs. The management of hope and depression should form an integral part of the palliative care provision. Advance care planning offers a framework to support communication between services and families. The symptoms experienced at end of life require specialist skills to manage and needs the support of a multidisciplinary team. References: . Whitehead B, O'Brien MR, Jack BA, Mitchell D. Experiences of dying death and bereavement in motor neurone disease: a qualitative study. Palliative Medicine [online] 2012;26(4):368–78. Available from: MEDLINE . Wood-Allum CA. Unanswered questions and barriers to research in the palliative care of motor neurone disease patients. Journal of Palliative Care [online] 2014;30(4):302–306. Available from: Academic Search Complete . NICE. Motor neurone disease: assessment and management NICE guidelines [NG42] [online]2016. Available from: https://www.nice.org.uk/guidance/cg105